Pengaruh Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Bandar Bakau Jaya Jakarta Utara - Dewi Kuntari; Bilgah Bilgah (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
A comfortable and good work environment is a collection of processes that encourage employee behavior and encourage the achievement of company goals. The work environment is things related to the workplace itself and can influence the way he does his work. This research aims to analyze the influence of the work environment on job satisfaction and employee performance at PT Bandar Bakau Jaya. This research used a questionnaire method with a Likert scale which was distributed to 37 respondents. The variables studied include work environment (X1), job satisfaction (X2), and employee performance (Y). Data analysis was carried out using descriptive statistics and data quality testing through validity and reliability tests. The research results show that a good work environment, such as adequate lighting, appropriate temperature, and good ventilation, has a positive influence on job satisfaction and employee performance. Most respondents agree that the conditions of their work environment affect productivity and the quality of work results. This research suggests that companies continue to improve working environmental conditions to increase employee satisfaction and performance.